Insights from African American Interpretation - Smith, Mitzi J. (Reading the Bible in the 21st century. Insights., 2017)
Each volume in the Insights series discusses discoveries and insights gained into biblical texts from a particular approach or perspective in current scholarship. Accessible and appealing to today's students, each Insight volume discusses how this method, approach, or strategy was first developed and how its application has changed over time; what current questions arise from its use; what enduring insights it has produced; and what questions remain for future scholarship. Mitzi J. Smith describes the distinctive African American experience of Scripture, from slavery to Black Liberation and beyond, and the unique angles of perception that an intentional African American interpretation brings to the text for a contemporary generation of scholars. Smith shows how questions of race,ethnicity, and the dynamics of "othering" have been developed in African American biblical scholarship, resulting in new reading of particular texts. Further, Smith describes challenges that scholarship raises for the future of biblical interpretation generally.